Factors affecting length of hospital stay in chronic obstructive pulmonary disease patients in a tertiary hospital of Nepal. - Pokharel, Pashupati (2021)
ABSTRACT: Background: Recent studies have shown increasing burden of chronic obstructive pulmonary disease (COPD) in Nepal. However, there are limited studies analyzing the potential factors associated with inpatient stay in COPD patients. So, this study is designed to find the factors associated with length of stay (LOS) in COPD patients in a tertiary teaching hospital of Nepal. Methods: This is a retrospective descriptive cross-sectional hospital-based study conducted between 2018 and 2020 on the patients admitted in the inpatient ward of pulmonary and critical care medicine of Tribhuvan University Teaching Hospital with a primary diagnosis of acute exacerbation of COPD (AECOPD). The sample size of our study was 90. Clinical, demographic and treatment parameters were analyzed to find the factors associated with length of stay. Results: The mean age of COPD patients was mean age 68.84 +- 1022 years and the average inpatient length of stay was 6.69 +- 4.02 days. Factors associated with length of stay are number of comorbidities, dyspnea grade at admission, eosinophils count at admission, use of inhalational medication and mechanical ventilator support. Conclusion: Our study has found the factors associated with length of stay in COPD patients in Nepal. These factors should be considered by clinicians during the treatment of COPD patients. Further prospective studies are required to analyze other factors and the hospital expenses associated with hospital stay in COPD patents. Keywords: Chronic obstructive pulmonary disease, Length of stay, factors, Nepal , Observational study.